Literature Review: Sikap dan Pengetahuan Catin Terhadap Pemeriksaan Hepatitis B dan HIV pada Skrining Pranikah - Manik, Frisca Anggraeni; Hapsari Windayanti; Rini Septianasari; Ikka Bella Seftiyani; Denil Shintiya; Dita Sintama (Universitas Ngudi Waluyo, 2023)
Marriage is a means of procreation and regeneration of the nation's human resources. Regeneration should be maintained in order to obtain superior human resources free from infectious diseases, including Hepatitis B (HBV) and Human Immunodeficiency Virus (HIV). In the midst of increasing prevalence of HIV and HBV from year to year globally and nationally, the rate of vertical transmission is also increasing. Screening examinations are needed to reduce mortality, morbidity, and the financial burden on the state. This is what drives the importance of premarital HBV and HIV screening for prospective brides (Catin). Differences in policy and program implementation make this policy not optimal. Several obstacles such as culture, education, economy, and stigmatization made it difficult to implement the program. This literature review research was conducted to examine the attitudes and behavior of premarital HIV and HBV screening for prospective brides and grooms. A total of 6 journals from pubmed and google scholar were reviewed after going through the inclusion criteria screening: Journals published in 2016 – 2023, in English or Indonesian, can be accessed in full text. The results of the review show that the catin volunteering rate for HBV and HIV testing is quite high, although this number can be maximized through premarital transmission education and counseling to increase confidence. Adult age, higher education, economic level, up to men showed higher results of understanding and volunteering for HIV and HBV testing. Reluctance to take tests tends to be caused by unpreparedness in dealing with the results (stigmatization) and post-test treatment. Support and socialization are needed either by friends, family, or educational/health institutions. Some of the strongest factors in motivating premarital Hepatitis B and HIV tests are knowledge, trust, norms, assurance of confidentiality, and costs. Thus, obstacles in the form of reluctance can be overcome through these things. Abstrak Pernikahan merupakan sarana prokreasi dan regenerasi sumber daya manusia bangsa. Regenerasi selayaknya dijaga agar didapatkan sumber daya manusia unggul terbebas dari penyakit menular, diantaranya Hepatitis B (HBV) dan Human Immunodeficiecy Virus (HIV). Di tengah meningkatnya prevalensi HIV dan HBV dari tahun ke tahun secara global dan nasional, angka penularan vertikal juga ikut meningkat. Dibutuhkan pemeriksaan screening guna mengurangi mortalitas, morbiditas, serta beban keuangan negara. Hal itulah yang mendorong pentingnya skrining HBV dan HIV Pranikah bagi Calon Pengantin (Catin). Perbedaan kebijakan dan pelaksanaan program membuat kebijakan ini tidak maksimal. Beberapa kendala seperti budaya, pendidikan, ekonomi, hingga stigmatisasi menjadikan hambatan dalam pelaksanaan program. Penelitian tinjauan Pustaka ini dilakukan untuk menelaah sikap dan perilaku skrining HIV serta HBV pranikah bagi calon pengantin. Sebanyak 6 jurnal bersumber pubmed dan google scholar ditelaah setelah melalui skrining kriteria inklusi: Jurnal terbitan tahun 2016 – 2023, Berbahasa Inggris atau Indonesia, dapat diakses secara full text. Hasil tinjauan menunjukkan cukup tingginya angka kesukarelaan catin terhadap pengujian HBV dan HIV, walaupun angka tersebut dapat dimaksimalkan melalui edukasi dan konseling pranikah terhadap penularan guna meningkatkan keyakinan. Usia dewasa, pendidikan tinggi, level ekonomi, hingga laki-laki menunjukkan hasil pemahaman serta kesukarelaan terhadap tes HIV dan HBV yang lebih tinggi. Keengganan melakukan tes cenderung diakibatkan ketidaksiapan dalam menghadapi hasil (stigmatisasi) dan pengobatan paska tes. Diperlukan dukungan dan sosialisasi baik oleh teman, keluarga, ataupun institusi Pendidikan/Kesehatan. Beberapa faktor terkuat dalam memotivasi pemeriksaan Hepatitis B dan HIV pranikah ialah pengetahuan, kepercayaan, norma, penjaminan kerahasiaan, hingga biaya dikeluarkan. Sehingga, kendala berupa keengganan dapat teratasi melalui hal-hal tersebut.